Removal of Ni (II) from Aqueous Solution by Adsorption onto Activated Carbon Prepared from Lapsi (Choerospondias axillaris) Seed Stone - Shrestha, Rajeshwar M.; Varga, Margit; Varga, Imre; Yadav, Amar P.; Pokharel, Bhadra P.; Pradhananga, Raja Ram (Journal of the Institute of Engineering, 2014)
Activated carbons were prepared from Lapsi seed stone by the treatment with H2SO4 and HNO3 for the removal of Ni (II) ions from aqueous solution. Two activated carbon have been prepared from Lapsi seed stones by treating with conc.H2SO4 and a mixture of H2SO4 and HNO3 in the ratio of 1:1 by weight for removal of Ni(II) ions. Chemical characterization of the resultant activated carbons was studied by Fourier Transform Infrared Spectroscopy and Boehm titration which revealed the presence of oxygen containing surface functional groups like carboxyl, lactones and phenols in the carbons. The optimum pH for nickel adsorption is found to be 5. The adsorption data were better fitted with the Langmuir equations than Freundlich adsorption equation to describe the equilibrium isotherms. The maximum adsorption capacity of Ni (II) on the resultant activated carbons was 28.25.8 mg g-1 with H2SO4 and 69.49 mg g-1 with a mixture of H2SO4 and HNO3. The waste material used in the preparation of the activated carbons is inexpensive and readily available. Hence the carbons prepared from Lapsi seed stones can act as potential low cost adsorbents for the removal of Ni (II) from water. DOI: http://dx.doi.org/10.3126/jie.v9i1.10680 Journal of the Institute of Engineering, Vol. 9, No. 1, pp. 166–174